Learning in a Small, Task–Oriented, Connectivist MOOC: Pedagogical Issues and Implications for Higher Education - Mackness, Jenny; Waite, Marion; Roberts, George; Lovegrove, Elizabeth (International Review of Research in Open and Distributed Learning, 2013)
Despite the increase in massive open online courses (MOOCs), evidence about the pedagogy of learning in MOOCs remains limited. This paper reports on an investigation into the pedagogy in one MOOC - Oxford Brookes University’s ‘First Steps in Learning and Teaching in Higher Education’ MOOC (FSLT12). FSLT12 was an open and free professional development opportunity for people moving into HE teaching. It was a small course (200 participants registered from 24 countries) which was focused on introducing HE teaching skills, and, uniquely, to deliberately integrate open academic practice as a vital part of professional development for HE teachers. A qualitative, case-study approach was used in the research, based on surveys, interviews, and social media, to provide evidence about how people learned in this course and consider wider implications for teaching and learning in higher education. The evidence shows that participants who completed the course were able to learn autonomously and navigate the distributed platforms and environments. The most challenging issues were acceptance of open academic practice and difficulty in establishing an academic identity in an unpredictable virtual environment. An interesting and significant feature of the course was the support for learners from a number of MOOC ‘veterans’ who served as role models and guides for less experienced MOOC learners. The research shows that small task-oriented MOOCs can effectively support professional development of open academic practice.